2015
DOI: 10.1080/01904167.2015.1069334
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen, Phosphorus and Potassium Fertilization Interactions on the Photosynthesis of Containerized Citrus Nursery Trees

Abstract: Downloaded by [New York University] at 20:03 24 July 2015 ACCEPTED MANUSCRIPT ACCEPTED MANUSCRIPT 2 The objective of this research was to evaluate the nitrogen, phosphorus and potassium (NPK) fertilizer effect on the development of 'Valencia' sweet orange nursery trees budded on Rangpur lime rootstocks in a greenhouse using containers. The experiment was a complete (1/5) 5 3 factorial randomized blocks design. Treatments comprised five concentrations (g per plant) of N (1.25; 6.25; 11.25; 16.25; 21.25); K (0.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
0
6
0
2
Order By: Relevance
“…Nitrogen (N) is a major nutritional element in plants, required in many physiological and developmental processes such as photosynthesis [1], metabolite biosynthesis [2,3] and flowering [4]. Most N uptake in fruit trees occurs during the intensive vegetative growth and post-harvest phases [5].…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen (N) is a major nutritional element in plants, required in many physiological and developmental processes such as photosynthesis [1], metabolite biosynthesis [2,3] and flowering [4]. Most N uptake in fruit trees occurs during the intensive vegetative growth and post-harvest phases [5].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Syvertsen (1987) reported that P level in leaves showed no relationship with photosynthetic in orange and pomelo seedlings. Bernardi et al (2015) reported that P had little interference on photosynthesis. Zambrosi et al (2013a) indicated that phosphorus uptake by young citrus plants in low-P soil depends on rootstock varieties and nutrient management.…”
Section: Discussionmentioning
confidence: 99%
“…Pagrindiniai fotosintezei būtini veiksniai yra šviesa ir CO2. Maisto medžiagos taip pat lemia fotosintezės procesų efektyvumą beveik visuose etapuose (Bernardini et al, 2015). Paprastai ankstyvaisiais augimo tarpsniais fotosintezės produktyvumas yra mažas, vėliau jis didėja ir maksimumą pasiekia maždaug iki žydėjimo (Fageria ir kt., 2006).…”
Section: įVadasunclassified